URGENSI RATIFIKASI KONVENSI ILO 188: PERLINDUNGAN HUKUM TERHADAP PEKERJA SEKTOR PERIKANAN INDONESIA - Lewiandy; Edwin Chandra (CV Rewang Rencang, 2024)
Indonesia is a maritime country. Indonesia has a significant workforce in fishing and maritime sectors work as crew members on foreign-flagged ship. However, Indonesia has not yet ratified the Internasional Labour Organization Convention No. 188 of 2017. This convention play crucial role in filling the legal gaps of ship crew member’s legal protection. ILO Convention 188 sets minimum standards for working conditions, wages, working hours, rest periods, living conditions, health and social insurance for crew members. Moreover, it does not require member states to adapt their domestic law. Thus, Indonesia has a strong legal basis to ratify ILO Convention 188.